Pengembangan Buku Ajar Visual Menulis Kreatif untuk Peserta Didik Madrasah Ibtidaiyah - Redite Kurniawan; Esa Nur Wahyuni; Zubad Nurul Yaqin (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2019)
Creative writing skills are still a challenge that must be faced by students of 6th grade in the Ar- Roihan Lawang Integrated Ibtidaiyah Madrasah. One of the contributing factor is the lack of interesting textbooks available at the school. This study aims to develop creative writing visual textbooks that improve students' skills in writing. This type of research is Research and Development (R & D) with the stage model Borg and Gall (2003). The stages include: needs analysis, product design, product development, product validity testing, testing on predetermined subjects, and product revisions. The results of this research and development of creative writing visual textbook products were based on the assessment of the media validator team with linguistic averages, presentation, graphics, scores of 4.72. Whereas from expert learning content with indicators of accuracy, attractiveness, and usability of 4, 29 are categorized very well. The product trial series found 33% addition in the experimental class post-test results and tested significantly with the number 0,000 SPSS t-test. Interviews in students indicated that creative writing visual textbook was very interesting so it can be concluded that this textbook product can improve the writing skills of 6th grade students of the Ibtidaiyah Ar-Roihan Lawang Madrasah.Keywords: Developing visual textbook, creative writing, writing skill.